ADVANTAGES OF TEACHING INFORMATION TECHNOLOGY TO ACADEMIC LYCEUM STUDENTS THROUGH INTERACTIVE METHODS - Omonova Muxtasar Rustamovna (TADQIQOTLAR, 2025)
Abstract  This article is dedicated to the advantages of teaching information technology to academic  lyceum  students  through  interactive  methods.  It  discusses  the  role  of interactive methods in the educational process, their impact on student motivation, and the effectiveness of knowledge acquisition. Practical examples and recommendations for using modern educational technologies are also provided.